Plan de negocios para una empresa de servicios de alquiler de menaje y local para eventos sociales en la ciudad de Machala de la provincia de El Oro - Espinoza Veintimilla, María José (2015)
This thesis was carried out with the aim of Developing a Business Plan for a company that hires local services and facilities for events in the city of Machala in the province of El Oro, given to the limited existing supply resulting in a deficiency in the service that it´s habitants receive from them. From the deductive method, it was inferred the need to create in the city a new alternative for rent facilities to develop social events. The inductive, analytical and descriptive methods that allowed to extract from the information gathered important data to create success strategiesfor this project. Also, some techniques were used to collect primary information suchasa field survey, an interview with managers of facilities: Oro Verde and Campos Verdes and La Opinion, which take 80% of the demand, and the technique of direct observation. The initial investment for the project is USD. 327.243,64 total costs in the first year of operation are USD.188.635,04; the estimated income is USD. 331.080,00allthese values are calculated for the base year. The Financial Evaluation was performed, reflecting very high levels of profitability, achieving a NPV of $350.918,60, an IRR of 34,64% and return on capital in the second year of operation, 1 month and 24 days. The project allows to increase of up to 23,75% % in costs and a decrease of 14,40% in revenues. With the information gathered, it is clear the advisability of investing in a company that provides citizens quality services in the rental of premises and facilities for events, and also to contribute to the development and enlargement of the city of Machala, its inhabitants, and consequently the country